Perivascular adipose tissue and coronary atherosclerosis - Mancio, J; Oikonomou, E; Antoniades, C (BMJ Publishing Group, 2018)
Adipose tissue (AT) is no longer viewed as a passive, energy-storing depot, and a growing body of evidence supports the concept that both quantitative and qualitative aspects of AT are critical in determining an individual’s cardiometabolic risk profile. Among all AT sites, perivascular AT (PVAT) has emerged as a depot with a distinctive biological significance in cardiovascular disease given its close anatomical proximity to the vasculature. Recent studies have suggested the presence of complex, bidirectional paracrine and vasocrine signalling pathways between the vascular wall and its PVAT, with far-reaching implications in cardiovascular diagnostics and therapeutics. In this Review, we first discuss the biological role of PVAT in both cardiovascular health and disease, highlighting its dual pro-atherogenic and anti-atherogenic roles, as well as potential therapeutic targets in cardiovascular disease. We then review current evidence and promising new modalities on the non-invasive imaging of epicardial AT and PVAT. Specifically, we present how our expanding knowledge on the bidirectional interplay between the vascular wall and its PVAT can be translated into novel clinical diagnostics tools to assess coronary inflammation. To this end, we present the example of a new computed tomography-based method that tracks spatial changes in PVAT phenotype to extract information about the inflammatory status of the adjacent vasculature, highlighting the numerous diagnostic and therapeutic opportunities that arise from our increased understanding of PVAT biology.